Analisis Kesalahan Tanda Baca pada Kumpulan Teks Opini dalam Website cnbcindonesia.com Edisi 2025 sebagai Bahan Literasi Bacaan Pelajar Guna Meningkatkan Pemahaman terhadap Kesalahan Tanda Baca - M. Yosi Maulana Hakim Saputra; Lintang Egan Dinda Maharani; Dhea Nabilla Ayu Setyoko; Dis Damara; Nor Rohmat Akbar Surahman; Asep Purwo Yudi Utomo; Desi Karolina Saragih; Winda Dwi Hudhana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research reviews punctuation errors that are not in accordance with the rules that have been determined based on grammatical standards. Similar errors are still found in opinion texts in the 2025 edition of the cnbcindonesia.com website, especially related to the use of punctuation marks. This study aims to analyze punctuation errors in a collection of opinion texts in the 2025 edition of the cnbcindonesia.com website. Another purpose of this research is as a reading literacy material for students to improve their understanding of punctuation errors. In this research, the author uses a qualitative descriptive methodological approach and a syntactic approach as a theoretical approach. The author obtained the study data by using the analysis technique of listening to readings from the collection of opinions as related references and recording information that can be used as data. The analysis is done by reading and marking errors in the news, then grouped to draw conclusions. This reason underlies the author in using listening and recording techniques in this research. The method in analyzing the data used by the author is the agih method. The author analyzes the text by identifying sentences that deviate from syntax rules and evaluating their feasibility as good and correct opinion texts. The analysis found several syntax errors in the form of punctuation errors that can affect the meaning or delivery of the message. In addition, this opinion text is worthy of being a student reading material to improve understanding because the errors are still tolerable and the structure is good.